Concentration and Subclass Distribution of Anti-ADAMTS13 IgG Autoantibodies in Different Stages of Acquired Idiopathic Thrombotic Thrombocytopenic Purpura - Sinkovits, György; Szilágyi, Ágnes; Farkas, Péter; Inotai, Dóra; Szilvási, Anikó; Tordai, Attila; Rázsó, Katalin; Réti, Marienn; Prohászka, Zoltán (Frontiers in Immunology, 2018)
Background: The acquired form of idiopathic thrombotic thrombocytopenic purpura (TTP) is an autoimmune disease, in which the underlying deficiency of the ADAMTS13 protease is caused by autoantibodies, predominantly of the IgG isotype. Certain HLA-DR-DQ haplotypes were associated with the risk of developing TTP. Objectives: To investigate the development of the ADAMTS13-specific antibody response during the course of the disease, we analyzed the concentration, subclass distribution, and inhibitory potential of anti-ADAMTS13 IgG autoantibodies in samples of TTP patients drawn during the first acute phase, in remission, and during relapse. Additionally, we compared the anti-ADAMTS13 IgG levels between patients carrying and not carrying risk and protective HLA-DR-DQ haplotypes. Patients and methods: We determined the anti-ADAMTS13 IgG concentration and subclass distribution in 101 antibody-positive samples of 81 acquired TTP patients by ELISA methods. The presence and semi-quantitative amount of anti-ADAMTS13 inhibitors were determined in 97 of 100 deficient samples, and the specific inhibitory potential of anti-ADAMTS13 autoantibodies were determined in 49 selected samples, by mixing ADAMTS13 activity assays. HLA-DR-DQ typing and haplotype prediction were performed in 70 of the above patients. Results: We found that IgG1 and IgG4 were the predominant subclasses, present in almost all samples. While IgG1 was the dominant subclass in almost half of the samples taken during the first acute episode, IgG4 was dominant in all samples taken during or following a relapse. The inhibitory potential of the samples correlated with levels of the IgG4 subclass. Anti-ADAMTS13 antibodies of IgG4-dominant samples had higher specific inhibitory potentials than IgG1-dominant samples, independently of disease stage. Interestingly, we found that patients carrying the protective DR7-DQ2 and DR13-DQ6 haplotypes had higher anti-ADAMTS13 IgG levels. Conclusion: Our results indicate that IgG4 becomes the dominant subtype at some point of the disease course, apparently before the first relapse, parallel to the increase in inhibitory potential of the anti-ADAMTS13 autoantibodies. Furthermore, we found an association between the genetic background and the antibody response in TTP.